Chicken or egg? Transport and urban development in Berlin - Kristoffer Moeller; Gabriel Ahlfeldt; Nicolai Wendland (European Regional Science Association (ERSA), 2013)
Infrastructure and especially mass transit play a major role in urban economics and are the centre of many research questions. Probably due to simultaneous determination of infrastructure supply and demand most research is only carried out on the supply side driven relationship explaining how transport leads to urban development. The intention of the paper is to provide a new and purely empirical perspective on the chicken-and-egg-problem. We propose a panel VAR approach employing a unique data set for historic Berlin between 1870 and 1936. We argue that it is of a planner?s interest to not only incorporate the supply side driven relationship but also the demand sided one. We turn the simultaneity problem into a purely empirical question since in practice it becomes difficult to derive theoretical implications from a comprehensive model that fully reflects all mutual interactions. Our analysis follows a twofold approach: Firstly, we estimate the interaction between population and transport. We then secondly extend the analysis by looking into the relation between land values and transport. Our estimates suggest a supply side driven relationship between transport and population and a positive reciprocal one between transport and land values. We conclude that new lines are not built entirely into undeveloped land but need to be connected to areas characterised by high land values to serve as a commuting mode.
Keywords: R12; R14; R41; N73; N74; 330; transport; Berlin; history; panel vector autoregression